If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -5(2x + -3(x + 6)) = -4(x + 5) Reorder the terms: x + -5(2x + -3(6 + x)) = -4(x + 5) x + -5(2x + (6 * -3 + x * -3)) = -4(x + 5) x + -5(2x + (-18 + -3x)) = -4(x + 5) Reorder the terms: x + -5(-18 + 2x + -3x) = -4(x + 5) Combine like terms: 2x + -3x = -1x x + -5(-18 + -1x) = -4(x + 5) x + (-18 * -5 + -1x * -5) = -4(x + 5) x + (90 + 5x) = -4(x + 5) Reorder the terms: 90 + x + 5x = -4(x + 5) Combine like terms: x + 5x = 6x 90 + 6x = -4(x + 5) Reorder the terms: 90 + 6x = -4(5 + x) 90 + 6x = (5 * -4 + x * -4) 90 + 6x = (-20 + -4x) Solving 90 + 6x = -20 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 90 + 6x + 4x = -20 + -4x + 4x Combine like terms: 6x + 4x = 10x 90 + 10x = -20 + -4x + 4x Combine like terms: -4x + 4x = 0 90 + 10x = -20 + 0 90 + 10x = -20 Add '-90' to each side of the equation. 90 + -90 + 10x = -20 + -90 Combine like terms: 90 + -90 = 0 0 + 10x = -20 + -90 10x = -20 + -90 Combine like terms: -20 + -90 = -110 10x = -110 Divide each side by '10'. x = -11 Simplifying x = -11
| k/2-3/5=k/3+1-10 | | 2(w+9)=-3(2w-1)+2w | | 1-K-6=0 | | 3(y-4)-5=-3(-5y+5)-4y | | 4(3x+x)+7-5x=8-5(5x-6x)+23 | | T^2-10000v^4=0 | | 2x-10=-9-8x | | 2x-10-2x+1=4(16-8x) | | -5x-4=7(x+8) | | 2-7n+5n=42-84 | | (n+3)*3=18 | | 0=-x+21.8 | | -3(w-9)=4w-43 | | 24x+27=-36x-8 | | 3x-40=5x+8 | | -256+a^4=0 | | 2(4a-2)=3(5+2a) | | 7x+42=2(x+1) | | x^3+2x^2-3x-10=0 | | 4.68+(-1.2)= | | -4x-3y=2 | | 25x+15=9x-7+10 | | 4.68+(1.2)= | | 5t-8k+w+9=55 | | 2(4a-2)=3(2+2a) | | f(x)=2x^2-20x+57 | | -2(m+3)=3(m-2) | | -8x-2y=-5 | | -8x-2y=5 | | 14t+5(1-5t)= | | -6xy+8+24xy+4= | | -1614x=9-9x |